Pengembangan Sumber Daya Pendidik - Mufidah, Yenny Imroatul (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Educators in the education process play a strategic role, especially in efforts to shape the character of the nation through the development of personality and desired values. The urgency of educators in the learning process is illustrated in the Arabic expression that was delivered by A. Malik Fadjar, "Al-Tariqah ahammu min al-maddah walakinna al-mudarris ahammu min al-tariqah (methods are more important than material, but educators are more important than methods). The development of educator resources in education is influenced by various aspects, including: the need to increase educator competency both theoretical and practical knowledge, the independence of educators to carry out professional development, support resources to carry out professional development, the willingness of educators as learners, and the ability of educators to actualize results development of professionalism which is demonstrated through the performance of educators and the effectiveness of educators in carrying out their duties. Improvement and development of educator resources starts from the acceptance of new educators. Selection of prospective educators needs to be done strictly in accordance with the requirements and conditions that have been determined